Camarillo State Hospital Meeting of Board Trustees (1964)
This document is a short summary of the agenda from a meeting of the board of trustees which occured on July 23, 1964. The meeting agenda consists of 5 topics: (1) At 12pm the meeting will occur in the office of the superintendent and have lunch. (2) There will be a meeting convened in Superintendent's Office by the Chairman. (3) Minutes will be read. (4) Discussion of the 1964-65 Operating and Capital Outlay Budget, including plans for remodeling the Receiving and Treatment Building. (5) Dr. Norman Mace will discuss the Seminar on Depressions.